(untitled) (Educação e Pesquisa, 2022)
Student assistance was constituted as support for students to remain in public higher education institutions, due to the financial difficulties of young people who usually moved from their hometowns to study elsewhere. Nowadays, however, new attributions have been delegated to student assistance to contribute to the educational process from an omnilateral perspective. This article aims to raise the possibilities of performance of student assistance professionals of formal education in contemporary society. To do so, bibliographic, and documental research was used as a strategy for data survey. We have identified that the possibilities of performance of student assistance run through two basic models: the first one is based on a selective policy, with a financial nature only, which reflects on a non-emancipating education; and the second one, of a universal nature which assists the student in several aspects: economic, social, academic, and human development. We understand this latter model because of the growing demands of today’s society and the consequent rise of other demands which impact academic performance and interfere with the permanence of students from different levels of education. Therefore, new roles can be attributed to student assistance to ensure the success of the educational process from an omnilateral perspective.